Autologous canine red blood cell transfusion using cell salvage devices. (14th January 2013) - Kellett‐Gregory, Lindsay M.; Seth, Mayank; Adamantos, Sophie; Chan, Daniel L.
Abstract Objective To describe the use of automated blood salvage devices for autotransfusion in dogs. Technique Blood salvage devices can be used to collect blood from the intraoperative surgical field or postsurgical drainage sites. The salvage device washes cells in 0.9% saline, removing plasma proteins, other cellular components, and activators of coagulation and inflammation. Washed red blood cells may be safely returned to the patient, minimizing the need for allogeneic blood transfusions. Significance Blood salvage has been safely used in human medicine for decades and is feasible in veterinary medicine. Potential advantages include reduced reliance on banked blood for massive transfusions and minimization of morbidities associated with the use of allogeneic and stored blood products. Concerns about the safety of salvaged blood have been largely dispelled in human medicine but further investigation regarding the safety of such procedures in veterinary patients is warranted.